Adenoid cystic carcinoma of the mandible with lung metastasis - Eren Yildirim; Mesut Sivri; Omer Demirtas; Mehmet Ertugrul Çiftçi; Gulen Kamak (Wolters Kluwer Medknow Publications, 2015)
Adenoid cystic carcinoma (ACC) is a malignant epithelial tumor of salivary glands. A 53-year-old man with intraosseous ACC in the mandible presented to our Faculty of Dentistry. Clinical examination revealed the swelling and enlarged local lymph nodes in the right mandibular area. After histopathological and radiological examination, ACC in the right mandibular molar area with lung metastasis was reported. We also review the literature.